PELMENI. WHERE THIS DISH COMES FROM - Korchagin, P.A. (Perm Federal Research Centre Journal, 2017)
Pelmeni appeared in the first half of the XVII century on the territory of Komi-Permyak okrug of Perm krai. They were first cooked at the snowy stops of the «Moscow path» in Kazarma and Chasovnia at a distance of 40 versts from the nearest settlements. The prototype of pelmeni was kundyumy-ushki - a vegetable dish (obviously of Turkic origin), which appeared in Russia in the first half of the XVI century. However, the people of Komi creatively reworked it into ferial mushroom ushki. But pelmeni have a special recipe and therefore it is impossible to speak about any idea, borrowed from the outside.